Tensions in the Mondragon coopitalist multinacionals - Anjel Errrasti (AECOOP Escuela de Estudios Cooperativos, 2014)
The Mondragon experience reflects the effort to combine the basic objectives of business development in international markets with job creation, the use of democratic methods in the organisation of the business and a commitment to the development of its social environment. The internationalisation of Mondragon cooperatives brings new dilemmas, paradoxes and contradictions for the Economic Democracy. This work analyses the case of the Mondragon cooperative-multinational Fagor Electrodomésticos. For many years Fagor has been growing via foreign direct investment, but the recent economic crisis has forced Fagor to establish radical job restructuring processes, both in the factories of the parent company in Mondragon and in its European affiliated companies, the French company Fagor- Brandt and the Polish firm Wrozamet, renamed Fagor-Mastercook. The analysis of the practices developed to downsize employment at Fagor pretends expand our understanding about the characteristics of the Mondragon multinationals and on the difficulties of spreading the cooperative model to subsidiaries.